Malaysian economic boom and crises: identifying the relationship between economic factors and economic growth / Nurfazihah Mohd Fadzli Yusof and Muhammad Haziq Faiz Abdul Aziz - Mohd Fadzli Yusof, Nurfazihah; Abdul Aziz, Muhammad Haziq Faiz (Faculty of Business and Management, 2016)
This study uses the data series of variable Import of Good and Services (IMPBOP), Export of Good and Services (EXPBOP), Inflation, Natural Resources Rents (Yield) and Foreign Direct Investment (FDI) to measure the relationship of these five Economics variables towards Gross Domestic Product (GDP). In addition, this study tries to investigate the best model to use among Single Linear Regression (SLR) or Multiple Linear Regression (MLR). This study also applies a time series procedure and the sample of this study is taken by yearly from 1984 to 2014. The findings show there is a significant positive relationship between Gross Domestic Product (GDP) and import of good and services (IMPBOP). There is a significant negative relationship between Gross Domestic Product (GDP) and export of good and services (EXPBOP). There is a significant negative relationship between Gross Domestic Product (GDP) and inflation. There is no significant positive relationship between Gross Domestic Product (GDP) and Natural Resources Rents (Yield). There is a significant positive relationship between Gross Domestic Product (GDP) and Foreign Direct Investment (FDI).